Larangan Perkawinan dalam UUP No 1 Tahun 1974 dan KHI Perspektif Filsafat Hukum Islam - Nastangin (MAHAKIM Journal of Islamic Family Law, 2020)
Rules for marriage restrictions are regulated in the Number Marriage Act. 1 of 1974 from Article 8-10 and also regulated in the Compilation of Islamic Law in Article 39, namely the prohibition for ever and Article 40-44, namely a temporary ban. The broadly outline, the contents of the rules on the marriage restrictions aresame, namely the prohibition of marriage with idolaters, marrying a woman who is still in the iddah period, marrying a stepmother, due to blood relations, intercession, stepchildren who are adherent with their mother, collecting two woman (muhrim). The purpose of this paper is to find out about the nature of the rules of marriage prohibition using the Philosophy approach of Islamic Law by explaining the nature and wisdom of its formal object. The conclusion of this paper is that there are rules for marriage restrictions to provide benefits to the community and someone who wants to get married because of the existence of these rules that not everyone can be married. This research is a library research (Library Reseach) by analyze various sources of laws relating to the prohibition of marriage. This research is also a qualitative research. According to Satori, qualitative research is descriptive because it describes an object, phenomenon or social setting that is translated in a narrative text. In line with the opinions of Surjono and Abdurahman, Dyah Ochtorina Susanti and A’an Efendi assert that doctrinal law research is systematic research on the rule of law regulate in certain areas of law, analyzing the relationship between one rule and another, explaining the difficult parts to be understood from a certain rule of law, it may even include predictions of the development of a certain rule of law in the future.